PENDEKATAN DAN STRATEGI NEGOSIASI DALAM NORMALISASI HUBUNGAN DIPLOMATIK AMERIKA SERIKAT - KUBA - Arie Siswanto (Universitas Kristen Satya Wacana, 2017)
The prolonged dispute originated from the Cold War era between the United States and Cuba has not been completely resolved yet, even after the two countries have re-established diplomatic ties. This paper discusses the factors affecting the on-going international negotiations between the US and Cuba, which include both constrainings as well as supporting factors, based on two aspects of negotiation, namely approach, and negotiation techniques. Based on the profile of the dispute, it is argued that integrative approach is the most appropriate approach to resolve disputes between the two countries. Meanwhile, future oriented process and emphasis on mutual interests are negotiation techniques that should be elaborated by both disputing parties in order to settle their dispute progressively.